THE EFFECT OF PERCEIVED WORK ENVIRONMENT ON FRONTLINE EMPLOYEES’ SERVICE RECOVERY PERFORMANCE: THE CASE OF FOUR AND FIVE STAR HOTELS IN JORDAN - Emad Y. Masoud; Tahreer Abu Hmeidan (European Scientific Journal, ESJ, 2013)
﻿﻿﻿﻿﻿Service recovery is a critical moment of truth and provides an opportunity for firms to please and retain customers. Service failure and recovery remain critical issues for both academicians and marketing practitioners. The study aimed to explore the potential effect of perceived working environment (training, empowerment, motivation, supportive management, and service technology) on frontline employees’ service recovery performance. A total of 400 frontline employees were chosen with simple random sampling method from 20 hotels in Amman, the capital of Jordan. Respondents were asked to complete the questionnaire in a self administered manner. 330 usable questionnaires were retrieved for a response rate of 82.5%. Structural Equations Model was used to verify the reliability and validity of the scale and to test the proposed model. The results showed that dimensions of working environment such as training, empowerment, motivation, supportive management, and service technology significantly predict frontline employees’ service recovery performance. Specifically, among the dimension of working environment, the most significant predictor of frontline employees’ service recovery performance was service technology and empowerment. This study implies that managers of four and five star hotels in Jordan should come forward and try their best to present a better work environment for frontline employees to enhance service recovery performance to maintain customers’ satisfaction.